(untitled) (Journal of the College of Basic Education, 2023)
This study aimed to identify the role of civil society organizations in promoting a culture of civil peace among young people in Tubas Governorate in the light of some variables (gender, age, work nature, monthly income). The researcher used the descriptive analytical approach due to its suitability for the purposes of the study. A questionnaire was designed to collect data that included (30) paragraphs, and after verifying the validity and reliability of the tool, it was distributed to the study sample members. The results of the study showed that: The total score for the first field (the role of civil society organizations in promoting a culture of civil peace) was medium, with an arithmetic mean of 3.41.The highest paragraph No. (2) came with an arithmetic average of (4.00), which states: Enhance the ability to appreciate the value of loyalty and belonging to the homeland and humanity. The total score for the second domain (the most important services provided by civil society organizations to young people) was high, with an arithmetic mean of 3.85.Where the highest paragraph No. (1) came with an arithmetic average of (4.40), which states: Seminars and conferences that benefit and develop youth are organized. The total score for the third domain (the positive aspects of the performance of civil society organizations) was medium, with an arithmetic mean of 3.41.Where came the highest paragraph No. (2) with a mean of (3.81), which states: It has a role in defending the rights of Palestinian youth. The total score for the fourth domain (pressures resulting from the negative performance of civil society organizations) was high, with an arithmetic mean of 3.75.The total score for the fourth domain (pressures resulting from the negative performance of civil society organizations) was high, with an arithmetic mean of 3.75. Through the results of the study, the researcher recommends the following: Holding youth conferences to increase their knowledge of social security and civil peace issues. Carrying out community activities that promote the development of a sense of individual responsibility for the security of the citizen and the homeland and the preservation of his capabilities. Increasing the effectiveness of the media and various social media in promoting the concept of social security and civil peace.